Analisa Desain Rangka Alat Compact Heat Induction Press Menggunakan Metode Finite Element Analysis - Ilham Taufik Maulana; Ahmad Zohari; Adik Susilo Wardoyo; Pilar Adhana Heryanto (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
In manufacturing technology, accuracy, effectiveness, and efficiency are important factors because the use of technology is expected to maximize quality and quantity with existing resources. The manufacturing process is the process of making products starting with the selection of raw materials and the machining process following the design to suit the needs. In other words, design is the main thing before carrying out manufacturing activities. Meanwhile, in designing a machine, it is necessary to have a material selection procedure according to the application conditions. The strength of the material can be obtained by simulating it using the Finite Element Analysis (FEA) method. This simulation aims to determine the maximum safe load limit on the tool frame design. In this study, the design of the tool frame made was given 5 loading treatments, the minimum loading was 50kg and the maximum loading was 200kg. Based on the simulation results, the maximum safety factor occurs at 50 kg loading of 10,019 ul and the minimum safety factor occurs at 200 kg loading with a value of 3.60064 ul. Based on the analysis of the load given to the frame of the compact press and sintering tool that the designed tool is safe.